1988
DOI: 10.1159/000275968
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ototoxic Diuretics (Loop Diuretics) on the Endolymphatic Sac

Abstract: The acute and chronic effects of treatment with ethacrynic acid (EA) and furosemide (FU) on the structure of the murine endolymphatic sac were studied by means of light and transmission electron microscopy. The animals were treated with loop diuretics in doses which are known to cause morphological alterations of the stria vascularis and a significant reduction of the endocochlear potential. A single intravenous injection of either EA or FU resulted in immediate morhpological changes such as an increase in cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 20 publications
(40 reference statements)
1
1
0
Order By: Relevance
“…It can be suggested that their modified shape could be induced by the increased imbibition of the subepithelial tissue which, for this reason, tends to exert a pressure on the nearby-located structures. An increased looseness of the perisaccular tissue was also observed after ethacrynic acid treatment, thus confirming the results of Erwall et al (1988). Moreover, an increased concentration of an organic matrix located subepithelially was also observed.…”
Section: Discussionsupporting
confidence: 84%
“…It can be suggested that their modified shape could be induced by the increased imbibition of the subepithelial tissue which, for this reason, tends to exert a pressure on the nearby-located structures. An increased looseness of the perisaccular tissue was also observed after ethacrynic acid treatment, thus confirming the results of Erwall et al (1988). Moreover, an increased concentration of an organic matrix located subepithelially was also observed.…”
Section: Discussionsupporting
confidence: 84%
“…Earlier studies have revealed similar ES changes after surgical labyrinthectomy [12] and in mice with hereditary type of cochleosaccular degeneration [13] as well as after administration of loop diuretics [14], In addition, installation of hypertonic hyaluronan in the middle ear results in an increased num ber of granular cells in the ES suggestive of an increased secretory activity [ 15]. This was interpreted as an effect of the hyperosmotic agent attracting water from the inner ear.…”
Section: Discussionmentioning
confidence: 87%